Detection of monoclonal free light chains by immunofixation electrophoresis and isoelectric focusing - comparison with the quantitative method of determination - Kušnierová, Pavlína; Zeman, David; Revendová, Kamila; Dlouhý, Ondřej (Scandinavian journal of clinical and laboratory investigation, 2020)
The study aimed to investigate free light chain (FLC) monoclonality in patients with an abnormal free kappa/lambda ratio (FLC ratio). Seventy serum samples with abnormal FLC ratio were examined using an immunoturbidimetry (Binding Site, SPA) and the two different enzyme-linked immunosorbent assays (1. Sebia diagnostic kit; 2. in house methods), the monoclonal or oligoclonal bands of (FLC) by immunofixation electrophoresis (IE) and isoelectric focusing followed by affinity immunoblotting (IEF/AIB). The reference interval was calculated by non-parametric percentile method. 5.7% of samples examined by IE were suspected of monoclonal character of FLCs, but subsequently monoclonality was refuted by more sensitive IEF/AIB method; 7%, resp. 2.9% of samples showed FLC kappa, resp. FLC lambda oligoclonal character of bands. A statistically significant dependence was found between FLC ratio (Sebia) and FLC ratio (SPA), rs = 0.510, p = .001. Kappa statistic evaluated a fair conformity between the FLC ratio (Sebia) and IEF/AIB (kappa = 0.468) and between FLC ratio (in house) and IEF/AIB (kappa = 0.300). The verified reference interval for FLC ratio (Binding Site) is between 0.35 and 2.18. The IEF/AIB is the most sensitive method to discriminate between monoclonal and oligoclonal bands of FLC. The Binding Site and Sebia diagnostic kits do not give consistent results. The Binding Site diagnostic kit provides more results above reference interval of FLC ratios. For routine decision on monoclonality of the FLC ratio (SPA) it is advisable to use a verified reference interval.
Keywords: dospělí; isoelektrická fokusace; Immunoglobulin lambda-Chains; Female; immunoturbidimetry; Free light chains; Adult; ženské pohlaví; Antibodies, Monoclonal; lidé; monoclonality; Aged, 80 and over; imunoglobuliny - lambda-řetězce; Blood Proteins; krevní proteiny; ELISA; Male; Aged; Isoelectric Focusing; oligoclonal bands; monoklonální protilátky; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans